(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
“The facebook image of a saint” is an elaboration of a hagiological issue – that is, regarding holiness. The reflection focuses on the question about the transformation of knowledge about the person and ethos of a Christian canonized in the Catholic Church, from the level of systematically developed data (objective image – classic, in theological sources) to the version adopted by the faithful and encoded in social statements (subjective image, on a social website “Facebook”). Three pages dedicated to the saints: Judah Thaddaeus, John Maria Vianney and Catherine-Kateri Tekakwitha were subjected to substantive analysis. On this basis, the hagiological image of the saint was described in the following types: apostle, authority, helper. A subjective element dominates in social statements, focused on satisfying individual spiritual and religious needs. The Facebook image of a saint is expressed in the form of prayers to saints, requests for intercession, their wisdom sentences and their photographic material referring to graphics, art and places associated with the saint. The biographical element is minimized. The Facebook images of saints promote the axiological and spiritual plane of the person and life of the saint. The transformation of religious knowledge takes place in the perspective of caring for the formation of Christian spirituality of the faithful. The leading theme, chosen for the Facebook image, is conversion, faithfulness to Jesus Christ, submission to the Holy Spirit, Christian love, forgiveness. This process shows that spiritual needs are not met by historical but axiological messages.